Rancang Bangun Sistem Informasi Pelatihan Pada Balai Diklat Industri (BDI) Padang Berbasis Mobile Application Menggunakan API - Suryamen, Haris; Wistia Rizalmi, Annisa; Wahyuni, Ullya Mega (ITP Press, 2024)
Balai Diklat Industri (BDI) Padang is an institution that focuses on training in the field of embroidery and fashion to develop the skills of individuals or groups. Currently, the training is operated using a web-based application through a laptop, but there are feature limitations that hinder the effectiveness of training management. The main problem related to the web application feature at this time is having too many menu features so that employees have to look for menus related to training, instructors have not been able to take attendance of participants through the web, and participants have not been able to access training activities that exist in BDI Padang. Therefore, BDI Padang wants to improve training management by developing a web application into a mobile application. In this development, API (Application Programming Interface) is used as an interface medium between systems, with the type of API used being RESTful API. RESTFul API acts as a bridge for data communication between clients and databases, with output in the form of JSON data. The programming language for Android uses Kotlin and Retrofit as a REST Client that retrieves and sends data through the RESTful API web service. System testing is done using the black box testing on all functionalities according to the initial system design. The test results show that all the functionalities designed run according to the system requirements. This research produces an Android system in the form of an application package file (APK) for the training information system at BDI Padang.